Prenatal Developmental Trajectories of Fluctuating Asymmetry in Bat Humeri - López-Aguirre, Camilo; Hand, Suzanne J.; Koyabu, Daisuke; Tu, Vuong Tan; Wilson, Laura A. B. (Frontiers in Cell and Developmental Biology, 2021)
Fluctuating asymmetry (random fluctuations between left and right sides of the body) has been interpreted as an index to quantify both the developmental instabilities and homeostatic capabilities of organisms, linking the phenotypic and genotypic aspects of morphogenesis. However, studying the ontogenesis of fluctuating asymmetry has been limited to mostly model organisms in postnatal stages, missing prenatal trajectories of asymmetry that could better elucidate decoupled developmental pathways controlling symmetric bone elongation and thickening. In this study we quantified the presence and magnitude of asymmetry during the prenatal development of bats, focusing on the humerus, a highly specialised bone adapted in bats to perform under multiple functional demands. We deconstructed levels of asymmetry by measuring longitudinal and cross-sectional asymmetry of the humerus, using a combination of linear measurements and geometric morphometrics. We tested the presence of different types of asymmetry and calculated the magnitude of size-controlled fluctuating asymmetry to assess developmental instability. Statistical support for the presence of fluctuating asymmetry was found for both longitudinal and cross-sectional asymmetry, explaining on average 16% of asymmetric variation. Significant directional asymmetry accounted for less than 6.6% of asymmetric variation. Both measures of fluctuating asymmetry remained relatively stable throughout ontogeny, but cross-sectional asymmetry was significantly different across developmental stages. Finally, we did not find a correspondence between developmental patterns of longitudinal and cross-sectional asymmetry, indicating that processes promoting symmetrical bone elongation and thickening work independently. We suggest various functional pressures linked to newborn bats’ ecology associate with longitudinal (altricial flight capabilities) and cross-sectional (precocial clinging ability) developmental asymmetry differentially. We hypothesise stable magnitudes of fluctuating asymmetry across development could indicate the presence of developmental mechanisms buffering developmental instability.